A SIMPLE ANALYSIS OF CHARACTER GROWTH IN YOUNG ADULT FICTION - Sharma, Mala (International Journal of Research -GRANTHAALAYAH, 2020)
The issue of character development is also a key feature of young adult (YA) fiction, which also undergoes the emotional, psychological, and social transformations of characters in their journey through challenges and life-altering events. In this paper, the authors investigate how conflict, decision making, relationships, and self-reflection help the YA literature to depict character development. Through the analysis of a few novels, it describes the general trends in the character development such as the process of innocence to maturity, exposure to personal and social challenges, and the growth of empathy, sturdiness, and ethical judgment. The paper also examines the ways in which literary devices like the first-person voice, inner dialogues, and plot development enhance the comprehension of the reader about the development of the main character. The knowledge of the character development in YA fiction not only informs the discussions of the elements of literary techniques but it also provides a glimpse of the psychology of adolescence, identity formation, and the role that literature plays in the social and emotional education of young readers. This paper provides emphasis on the role of YA literature as an educational resource and a way to embrace self-awareness and critical thinking in teenagers.